Robotic repair of atrial septal defect: Pre-groove vertical right atriotomy approachCentral MessagePerspective - Kitae Kim, MD; Yun Seok Kim, MD; Hong Rae Kim, MD, PhD; Ho Jin Kim, MD, PhD; Jae Suk Yoo, MD, PhD; Joon Bum Kim, MD, PhD; Sung-Ho Jung, MD, PhD; Jae Won Lee, MD, PhD (JTCVS Techniques)
Objective: Minimally invasive repair using robotic systems has been accepted as an attractive alternative in the surgical repair of atrial septal defects (ASDs). Clear exposure of the entire rim of the ASD is often hindered during a robotic approach. Here, we describe an approach using vertical right atriotomy along the interatrial groove that may enhance the exposure of the ASD. Methods: Patients who underwent ASD closure using the da Vinci Si surgical ystem (Intuitive Surgical) from 2007 to 2021 were included. During ASD closure procedures, right atriotomy was performed either conventionally in an oblique manner or parallel to the interatrial groove. A comparative analysis was performed in terms of all-cause mortality, complications, and durations of cardiopulmonary bypass, aortic crossclamp, intensive care unit stay, and hospital stay. The inverse probability of treatment weighting was utilized to balance baseline characteristics across different surgical approaches. Results: A total of 114 consecutive patients (mean age, 38.7 ± 12.8 years) constituted the study cohort. There were no cases of mortality or surgical complications in either group. After adjusting for potential covariates, the cardiopulmonary bypass (92.8 ± 31.5 minutes vs 143.1 ± 40.7 minutes) and aortic crossclamp (30.7 ± 21.3 minutes vs 60.8 ± 23.5 minutes) times were significantly shorter in the group using vertical right atriotomy than in the group using conventional approach (P < .001 for both). Conclusions: Performing vertical right atriotomy adjacent to the interatrial groove optimized ASD exposure compared with the conventional approach during robotic ASD repair, leading to reduced cardiopulmonary bypass and aortic crossclamp times.